2010
DOI: 10.1371/journal.ppat.1000993
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Galectin-1 Binds to Specific Glycans on Nipah Virus Fusion Protein and Inhibits Maturation, Mobility, and Function to Block Syncytia Formation

Abstract: Nipah virus targets human endothelial cells via NiV-F and NiV-G envelope glycoproteins, resulting in endothelial syncytia formation and vascular compromise. Endothelial cells respond to viral infection by releasing innate immune effectors, including galectins, which are secreted proteins that bind to specific glycan ligands on cell surface glycoproteins. We demonstrate that galectin-1 reduces NiV-F mediated fusion of endothelial cells, and that endogenous galectin-1 in endothelial cells is sufficient to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 62 publications
5
78
0
3
Order By: Relevance
“…After pH-dependent cleavage, fusion-active F 1 -F 2 must then recycle back to the plasma membrane before cell-to-cell fusion can occur. As shown previously by others and us, F cleavage efficiencies differ significantly depending on the cell line (1,7,24,48,53). We found F processing rates to vary between 20 and 70% in cells from different species and tissues or in cell lines stably transfected with NiV glycoproteins.…”
Section: Niv F Cleavage Efficiency Varies Between Different Cell Typessupporting
confidence: 84%
“…After pH-dependent cleavage, fusion-active F 1 -F 2 must then recycle back to the plasma membrane before cell-to-cell fusion can occur. As shown previously by others and us, F cleavage efficiencies differ significantly depending on the cell line (1,7,24,48,53). We found F processing rates to vary between 20 and 70% in cells from different species and tissues or in cell lines stably transfected with NiV glycoproteins.…”
Section: Niv F Cleavage Efficiency Varies Between Different Cell Typessupporting
confidence: 84%
“…in other studies (7,23,26), to demonstrate that galectin-1 inhibits influenza virus infection by direct binding to galactosecontaining glycans on the viral envelope, inhibiting viral hemagglutination activity, and blocking viral entry. Moreover, compared to previous in vitro studies on the effects of galectin-1 on viral infection (23,30), our study is the first to show in vivo that galectin-1 can ameliorate influenza virus pathogenesis through direct anti-influenza virus activity.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that recombinant human galectin-1 inhibits cell fusion and syncytial formation mediated by the fusion (F) envelope glycoprotein of Nipah virus through binding to specific N-glycans in the F glycoprotein (23). Such effects were also demonstrated recently in endothelial and neural cells, the targets of Nipah virus infection (7). However, galectin-1 was also reported to increase HIV-1 infectivity through stabilization of virus attachment to host cells (26,30).…”
mentioning
confidence: 94%
“…Vascular endothelial cells express several galectin family members, including galectin-1 and -9. For example, infection of vascular endothelial cells with Ebola virus results in endothelial cell activation (9) and increased expression of galectin-1 (10,11). Infection of endothelial cells with Dengue virus induces expression of galectin-9 (12), as does binding of double-stranded RNA to Toll-like receptor 3 on endothelial cells (13).…”
mentioning
confidence: 99%
“…Using NiV-F/G-pseudotyped particles, our labs previously demonstrated that galectin-1 produced by endothelial cells can inhibit endothelial cell syncytium formation mediated by NiV-G and NiV-F (11,24). In these studies, galectin-1 reduced NiV-F mediated fusion of endothelial cells by interfering with NiV-F maturation, reducing lateral mobility of NiV-F on the plasma membrane and inhibiting the conformational change in NiV-F triggered by receptor binding to NiV-G that is necessary for cellcell fusion (11).…”
mentioning
confidence: 99%